Buletin Peternakan : KUALITAS NUTRISI AMPAS KELAPA (Cocos nucifera L.) FERMENTASI MENGGUNAKAN Aspergillus niger - Heri Kurniawan (Peternakan UGM, 2016)
This research was aimed to observe the effect of usage of Aspergillus niger for fermenting coconut dregs (Cocos Nucifera L.) on its nutrition quality. Aspergillus niger obtained from Biochemical and Nutrition Laboratory of Animal Science Faculty on UGM, Yogyakarta was optimalized at coconut oil and coconut dregs as substrat.